Open Source Messaging Application Development Building and Extending Gaim - Egan, Sean.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
Are you enamored with instant messaging? Would you like to learn how to create your own messaging application? This book shows you how, by dissecting Gaim—the world's most popular open source instant messaging application. Authored by the Gaim maintainer, Sean Egan, you are presented with a thorough overview of Gaim architecture and application programming interface. You'll learn how to make the most of the popular GTK+ graphical user interface toolkit. Egan guides you through the creation and installation of plug-ins, and discusses strategies involved in supporting messaging protocols like MSN Messenger, AIM and IRC. He also covers topics such as multi-platform support and internationalization.
Getting Started -- The Open Source Development Process -- Development Tools -- Programming Gaim -- GTK+ Basics -- Advanced GTK+ -- Sockets -- Protocol Plug-Ins -- Internationalization -- Portability.
Keywords: Open source software; Computer programming; Software engineering; Open Source; Software Engineering/Programming and Operating Systems